Effectiveness of Photobiomodulation in pain associated with Burning Mouth Syndrome: A systematic review (Research, Society and Development, 2025)
Objective To evaluate the effectiveness of low-level laser in reducing pain associated with Burning Mouth Syndrome. Method A systematic review was carried out, analyzing randomized clinical trials (RCTs) that compared the use of low-level laser with another treatment strategy to reduce pain in patients with BMS. The studies were selected through search in the databases PubMed (including Medline), Scopus, Embase, SciELO, Web of Science, Latin American and Caribbean Health Sciences (LILACS) and Cochrane until November 30, 2022, and updated on October 30, 2023. Results Eight RCTs which included 183 study participants and 150 controls were identified. The studies showed a higher percentage of women affected by BMS in relation to men. The predilection sites were the tongue, buccal mucosa and lip. Individuals irradiated with the laser showed improvement at the end of the intervention. Conclusion The use of low-level laser can be a therapeutic option for controlling the painful symptoms caused by BMS, as well as, indirectly, the associated emotional aspects. However, according to the diversity of photobiomodulation protocols found, new studies need to be developed to standardize laser therapy parameters for BMS and, thus, evaluate the control of painful symptoms longitudinally.